2017
DOI: 10.1016/j.ajpath.2017.08.011
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic Tmem30a Deficiency Causes Intrahepatic Cholestasis by Impairing Expression and Localization of Bile Salt Transporters

Abstract: Mutations in ATP8B1 or ATP11C (members of P4-type ATPases) cause progressive familial intrahepatic cholestasis type 1 in human or intrahepatic cholestasis in mice. Transmembrane protein 30A (TMEM30A), a β-subunit, is essential for the function of ATP8B1 and ATP11C. However, its role in the etiology of cholestasis remains poorly understood. To investigate the function of TMEM30A in bile salt (BS) homeostasis, we developed Tmem30a liver-specific knockout (LKO) mice. Tmem30a LKO mice experienced hyperbilirubinemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Quantitative PCR was employed as the principle technique for measurement of the expression of bile acid transporters because it can offer more precise quantitation than measurement of protein expression by western blot and can more readily be applied to the assay of multiple samples generated in dose-response experiments. Other studies of bile acid transporter expression have shown a good correlation between results obtained using qPCR and those obtained using western blot (Liu et al, 2017;Weerachayaphorn et al, 2009;Weerachayaphorn et al, 2012).…”
Section: Extraction Of Rna and Quantitative Pcrmentioning
confidence: 73%
“…Quantitative PCR was employed as the principle technique for measurement of the expression of bile acid transporters because it can offer more precise quantitation than measurement of protein expression by western blot and can more readily be applied to the assay of multiple samples generated in dose-response experiments. Other studies of bile acid transporter expression have shown a good correlation between results obtained using qPCR and those obtained using western blot (Liu et al, 2017;Weerachayaphorn et al, 2009;Weerachayaphorn et al, 2012).…”
Section: Extraction Of Rna and Quantitative Pcrmentioning
confidence: 73%
“…16 Two studies about the functions of Tmem30a have been performed in the retina and liver, respectively, by using Tmem30a tissue-specific deletion mouse models. 16,20 Deletion of Tmem30a resulted in a loss of PS flippase activity and exposure of PS on cell outer surface. 16,20 Tmem30a deficiency in mouse cone cells results in loss of cone cells and impaired photopic electroretinogram responses in the retina.…”
mentioning
confidence: 99%
“…16,20 Deletion of Tmem30a resulted in a loss of PS flippase activity and exposure of PS on cell outer surface. 16,20 Tmem30a deficiency in mouse cone cells results in loss of cone cells and impaired photopic electroretinogram responses in the retina. 16 Currently, the physiologic roles of Tmem30a in hematopoietic cells are unknown.…”
mentioning
confidence: 99%
“…P4-ATPases are members of a family of proteins that transport aminophospholipids from the exoplasmic to the cytoplasmic leaflet of cell membranes by utilizing ATP, thereby maintaining the aminophospholipid asymmetry in the cellular membrane (Halleck et al, 1999;Holthuis and Levine, 2005). Several P4-ATPases have been reported to have important functions in physiological and pathological conditions (Bull et al, 1998;Cacciagli et al, 2010;Darland-Ransom et al, 2008;Wang et al, 2004;Liu et al, 2017;Zhang et al, 2017). By using RT-PCR, we demonstrated that eight of 14 P4-ATPases are expressed in HRECs (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…These genes encode N-glycosylated proteins with two transmembrane domains and play critical roles in the folding and function of P4-ATPases (Katoh and Katoh, 2004;van der Velden et al, 2010). Our previous studies have demonstrated the essential roles of the TMEM30A gene in retinal development, bile salt transportation and the survival of hematopoietic cells (Li et al, 2018;Liu et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%